MENGENAL DAN MENGGUNAKAN MICROSOFT EXCEL DALAM PENGELOLAAN DATA (DASAR) - Kuswandi Kuswandi (JURNAL ABDIMAS PLJ, 2021)
Basic data management using Microsoft Excel tools is the initial material given in studying functions in Microsoft Excel so that all participants, both beginners and those who have studied  before, can easily understand and practice, while the material given starts from understanding Microsoft Excel. , advantages and disadvantages, operators, basic mathematical formulas and calculation functions. the purpose of holding community service with this theme is so that people can easily and practice how to manage data in the form of calculations to reporting using Microsoft Excel so that work will be completed faster when compared to manual management. This service is carried out using a practical method through case study questions given, due to the implementation under the conditions of Covid 19, the learning method is provided online using google meet.Keywords: Microsoft excel, management, basic data, dedication, excel basic formula